Dependence of longevity of composite restoration from polymerization time during restoration of class II cavities (LLC "Endo Press", 2020)
The restoration of class II cavities always requires using of matrix system. Generally, in the directions for use of materials is not specified the need of further restoration polymerization after matrix removal from the vestibular and oral surfaces. Some doctors give additional curing, some do not. Evidence-based medicine does not provide any recommendations about that. Inadequate curing time can lead to incomplete composite polymerization, in consequence of which fragmentary restoration chipping may occur.